Romanticism : keywords - Burwick, Frederick (Hoboken : John Wiley & Sons Inc., 2015)
'Compiles 70 of the key terms most frequently used or discussed by authors of the Romantic period - and most often deliberated by critics and literary historians of the era. Offers an indispensable resource for understanding the ideas and differing interpretations that shaped the Romantic period Includes keywords spanning Abolition and Allegory, through Madness and Monsters, to Vision and Vampires Features in-depth descriptions of each entry's direct meaning and connotations in relation to its usage and thought in literary culture Provides deep insights into the political, social, and cultural climate of one of the most expressive periods of Western literary history Draws on the author's extensive experience of teaching, lecturing, and writing on Romantic literature'--
'Romanticism Keywords offers readers an invaluable collection of 70 key terms most frequently discussed by authors of the Romantic period--and most often deliberated and debated by contemporary critics and literary historians of the era'--
Machine generated contents note: Introduction A Abolition Allegory Antiquarianism Art for Art's Sake Associationism Autobiography B Bardolatry Bluestockings C Childhood Colonialism Crime D Dandyism Dialectics Dreams E Ekphrasis Eroticism F Folklore G Genius Gothic Grotesque Gusto H Harlequinade Hellenism Higher Criticism Homosexuality I Illusion Imagination Imitation Incest Inspiration M Madness Medievalism Melancholy Melodrama Mesmerism Metaliterature Metonomy Monsters Mythopoeia N Nature Necessitarianism Negative Capability O Organicism Orientalism P Pantheism Parody Passion Pathetic Fallacy Picturesque Poetic Form Prometheus R Reflection Reform Religion Revolution Rights Romanticism Romantic Irony Ruins S Satire Science Sensibility Solitude Sublime Supernaturalism Symbol Sympathy T Transcendentalism Translation Travel V Vampire Aesthetics Vision W Women's Rights Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Romanticism -- Dictionaries; Romanticism -- History and criticism -- Handbooks, manuals, etc; English language -- Etymology; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English language -- Etymology; Romanticism; Electronic books; Criticism, interpretation, etc; Dictionaries; Handbooks and manuals; Electronic books